A mixing dynamical system on the cantor set - Jeong H. Kim (International Journal of Mathematics and Mathematical Sciences)
In this paper we give mixing properties (ergodic, weak-mixng and strong-mixing) to a dynamical system on the Cantor set by showing that the one-sided (12,12)-shift map is isomorphic to a measure preserving transformation defined on the Cantor set